Advancing climate resilience: technological innovations in plant-based, alternative and sustainable food production systems - Aleksandar Mešić; Marina Jurić; Francesco Donsì; Luna Maslov Bandić; Slaven Jurić (Discover Sustainability)
Abstract Sustainable food production is becoming essential, and a shift from traditional practices to more responsible alternatives aiming to generate nutritious, safe, and accessible food while minimizing environmental impacts is crucial. This review article discusses the importance of sustainable food production technologies in meeting global food demand while addressing problems regarding climate change. Some of the key technologies include precision agriculture, hydroponics, aquaponics and vertical farming. Precision agriculture uses technology to enhance farming efficiency by gathering data on soil and water variations and optimizing practices like planting, fertilization, and irrigation. Hydroponics and aquaponics are other alternatives for growing plants using as much as 90% less water and producing more food compared to conventional methods, while vertical farming can increase crop yield per land area, particularly in urban settings, due to its potential to reduce the strain on conventional agricultural land suitable for urban regions. Additionally, genetic modification can help create desirable traits of some plants making them plausible to integrate in vertical farming systems, but this requires careful management. Furthermore, nanotechnology is emerging as another method poised to transform agriculture by providing sustainable and efficient solutions for nutrient regulation, plant growth, and disease resistance whereas Agriculture 5.0 combines traditional agriculture with modern technologies to improve sustainable food production. Finally, alternative protein sources, such as plant-based, insects, cultured meat, mycoprotein and microalgae have emerged as a sustainable solution to traditional meat production. Integrating the abovementioned technologies into agricultural practices is crucial for achieving multiple Sustainable Development Goals.